Transforming universities with digital distance education : the future of formal learning - Nichols, Mark (New York, NY : Routledge, 2020)
"Transforming Universities with Digital Distance Education explores the ways in which higher education stakeholders can apply and leverage the benefits of online learning. Systems-wide access, scale, and quality are achievable goals but require forms of teamwork and financial modelling beyond those at the instructor or program level. This book's organizational view tackles the systems and practices that will help senior managers and decision-makers guide an entire institution away from dysfunction-incremental progress, insufficient capacity, high costs, and generic products-and toward the macro-level implementation and operations of effective online pedagogies"--
1. Introduction -- 2. On learning and formal education -- 3. Models of university education -- 4. The digital distance education (DDE) model -- 5. Module narratives -- 6. Teaching roles -- 7. Module development : context, direction and practice -- 8. Operating models and organisational change.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: Distance education -- Computer-assisted instruction; Internet in higher education; Educational change; Education, Higher -- Effect of technological innovations on; Enseignement à distance -- Enseignement assisté par ordinateur; Internet dans l'enseignement supérieur.; Enseignement -- Réforme.; Enseignement supérieur -- Effets des innovations sur; Distance education -- Computer-assisted instruction; EDUCATION -- General